2022
DOI: 10.1161/jaha.122.025257
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Likelihood of Disease Pathogenicity Among Incidentally Identified Genetic Variants in Rare Dilated Cardiomyopathy‐Associated Genes

Abstract: Background As utilization of clinical exome sequencing (ES) has expanded, criteria for evaluating the diagnostic weight of incidentally identified variants are critical to guide clinicians and researchers. This is particularly important in genes associated with dilated cardiomyopathy (DCM), which can cause heart failure and sudden death. We sought to compare the frequency and distribution of incidentally identified variants in DCM‐associated genes between a clinical referral cohort with those in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 130 publications
0
3
0
Order By: Relevance
“…The original report by Brauch et al 19 identified 6 pathogenic variants in RBM20 all located within the RS domain, in what, based on our recent work, 30 we now know to be the core NLS. Since this initial study, many additional RBM20 variants have been reported both in and outside the RS domain in association with disease, 13,20,26,46,48,49,52,53,55,56,59–88 and the number continues to increase. Although variants have now been identified throughout the RBM20 protein, the windows c.1881–1920 (encoding the NLS in exon 9) and c.2721–2760 (encoding a portion of the glutamate-rich region in exon 11) represent the 2 currently accepted hotspots for DCM-associated variants (Figure 1B and 1C).…”
Section: Variants In the Rbm20 Nls Are Causative In Aggressive Dcmmentioning
confidence: 99%
“…The original report by Brauch et al 19 identified 6 pathogenic variants in RBM20 all located within the RS domain, in what, based on our recent work, 30 we now know to be the core NLS. Since this initial study, many additional RBM20 variants have been reported both in and outside the RS domain in association with disease, 13,20,26,46,48,49,52,53,55,56,59–88 and the number continues to increase. Although variants have now been identified throughout the RBM20 protein, the windows c.1881–1920 (encoding the NLS in exon 9) and c.2721–2760 (encoding a portion of the glutamate-rich region in exon 11) represent the 2 currently accepted hotspots for DCM-associated variants (Figure 1B and 1C).…”
Section: Variants In the Rbm20 Nls Are Causative In Aggressive Dcmmentioning
confidence: 99%
“…In 2015, the American College of Medical Genetics and Genomics issued a policy statement recommending that only likely pathogenic/pathogenic (LP/P) variants found in 59 genes that were believed to be clinically actionable should be reported (Yang et al, 2022). Some DCM‐associated genes were included in this ACMG‐59 list, but many of the rare ones were not, although the list continues to evolve.…”
mentioning
confidence: 99%
“…Now, newly published research has identified specific DCM genes (not all DCM genes) that were more likely to have rare variants identified in individuals undergoing ES for reasons unrelated to their heart (Yang et al, 2022). Conversely, incidental variants found in FLNC , RBM20 , MYH6 , DSP , ABCC9 , JPH2 , and NEXN had the greatest chance of DCM association.…”
mentioning
confidence: 99%